2005
DOI: 10.1118/1.1836291
|View full text |Cite
|
Sign up to set email alerts
|

Rest period duration of the coronary arteries: Implications for magnetic resonance coronary angiography

Abstract: Magnetic resonance (MR) and computed tomography coronary imaging is susceptible to artifacts caused by motion of the heart. The presence of rest periods during the cardiac and respiratory cycles suggests that images free of motion artifacts could be acquired. In this paper, we studied the rest period (RP) duration of the coronary arteries during a cardiac contraction and a tidal respiratory cycle. We also studied whether three MR motion correction methods could be used to increase the respiratory RP duration. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…The purpose of this study was to measure the three-dimensional (3-D) displacement and velocity of the coronary arteries from free breathing coronary angiograms, and to understand the individual contributions of the cardiac contraction and breathing. This study complements a recently published report on the rest periods of the coronary arteries during the cardiac and respiratory cycles [6].…”
supporting
confidence: 87%
“…The purpose of this study was to measure the three-dimensional (3-D) displacement and velocity of the coronary arteries from free breathing coronary angiograms, and to understand the individual contributions of the cardiac contraction and breathing. This study complements a recently published report on the rest periods of the coronary arteries during the cardiac and respiratory cycles [6].…”
supporting
confidence: 87%
“…For example, Shechter et al (2005a) reported that the motion of the left coronary artery was largely rigid-body, whereas that of the right coronary artery was better represented by an affine transform. Therefore, one possible cause for the echo-only technique performing worse away from the left ventricle is that the motion on the right side of the heart has a larger affine component.…”
Section: Discussionmentioning
confidence: 98%
“…48 Typically it occurs in early to mid diastole and is around 110 ms for the left coronary artery and 65 ms for the RCA. 43 However, in patients with fast heart rates, the end systolic pause may be longer and imaging would best be performed at this time. 50 Although 3D cine coronary angiography has been proposed using radial 3 and Cartesian 5 approaches, the temporal resolution achievable is limited and the rationale behind this approach has largely been to avoid the need for determining a subject-specific trigger time and acquisition window, and to enable averaging over those phases where motion is minimal to improve signal-to-noise ratio.…”
Section: Introductionmentioning
confidence: 99%